Nitric oxide-mediated regulation of ferroportin-1 controls macrophage iron homeostasis and immune function in Salmonella infection - Nairz, Manfred; Schleicher, Ulrike; Schroll, Andrea; Sonnweber, Thomas; Theurl, Igor; Ludwiczek, Susanne; Talasz, Heribert; Brandacher, Gerald; Moser, Patrizia L.; Muckenthaler, Martina; Fang, Ferric C.; Bogdan, Christian; et al. (Journal of experimental medicine, 2013)
Nitric oxide (NO) generated by inducible NO synthase 2 (NOS2) affects cellular iron homeostasis, but the underlying molecular mechanisms and implications for NOS2-dependent pathogen control are incompletely understood. In this study, we found that NO up-regulated the expression of ferroportin-1 (Fpn1), the major cellular iron exporter, in mouse and human cells. Nos2−/− macrophages displayed increased iron content due to reduced Fpn1 expression and allowed for an enhanced iron acquisition by the intracellular bacterium Salmonella typhimurium. Nos2 gene disruption or inhibition of NOS2 activity led to an accumulation of iron in the spleen and splenic macrophages. Lack of NO formation resulted in impaired nuclear factor erythroid 2-related factor-2 (Nrf2) expression, resulting in reduced Fpn1 transcription and diminished cellular iron egress. After infection of Nos2−/− macrophages or mice with S. typhimurium, the increased iron accumulation was paralleled by a reduced cytokine (TNF, IL-12, and IFN-γ) expression and impaired pathogen control, all of which were restored upon administration of the iron chelator deferasirox or hyperexpression of Fpn1 or Nrf2. Thus, the accumulation of iron in Nos2−/− macrophages counteracts a proinflammatory host immune response, and the protective effect of NO appears to partially result from its ability to prevent iron overload in macrophages
Gesehen am 24.11.2021